PERAN GURU DALAM MENINGKATKAN LITERASI SISWA MELALUI PROGRAM POJOK BACA DI MI MANSYAUL HUDA GUNUNGSARI BOJONEGORO - Fany Anggie Rahmawati; Prisca Budi Juvitasari (Program Studi Diploma Tiga Ilmu Perpustakaan Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2022)
Literacy is one aspect as a basic ability that must be possessed by someone, not only in educational institutions but in broad community forums. A person's literacy ability will make it easier for someone to understand and receive information. The aims of this study are: 1) To analyze the role of teachers in utilizing the reading corner program at MI Mansyaul Huda Gunungsari Bojonegoro. 2) To analyse the supporting and inhibiting factors of the reading corner program at MI Mansyaul Huda Gunungsari Bojonegoro. This research approach uses descriptive qualitative. Data collection techniques in this study used interviews and documentation. Meanwhile, the data analysis used the Miles and Hubberman method. The results of this study indicate that through the Reading Corner Program implemented by MI Mansyaul Huda Gunungsari Bojonegoro, there are several identified teacher roles in improving students' literacy skills, namely the teacher being a facilitator and evaluator, the teacher being the person in charge of providing understanding, and the teacher encouraging students' literacy skills, through learning activities or the available Reading Corner Program. Supporting and inhibiting factors in this study, namely the first supporting factors, namely facilities, school culture, and community encouragement. Factors inhibiting student interest in learning and an environment that is not conducive. Supporting or inhibiting factors are important for teachers or educational institutions to identify, especially as a form of evaluation so that the learning carried out can run even better.